Friend Request from Education”: The need for Social Media Policy for Educational Institutions in India - Deshmukh, Ajita (Indian Journal of Educational Technology, 2024)
The ubiquitous presence of Social Media in all fields in the current times cannot be denied. Exploring the possibilities of social media and its innovative use has become a fundamental skill in this era. The field of education, which had always distanced itself from social media, has finally come to accept social media at least as a channel for educational communication, especially during the COVID-19 scenario. This has raised several concerns ranging from privacy issues, cyberbullying, and surveillance to muffling of voices under the guise of discipline in educational institutions in India. This paper recognizes the lack of awareness of rights in digital spaces. The paper points out instances of social media policy framing becoming restrictive. This paper calls attention to the glaring absence of such guidelines and highlights the need for social media policy guidelines for educational institutions in India in order to overcome these concerns. This paper recommends the formulation of guidelines for educational institutions in India by an autonomous panel of experts from multidisciplinary domains.